Le amiche [videorecording (DVD)] - Antonioni, Michelangelo; Rossi-Drago, Eleonora, 1925-2007; Fabrizi, Franco, 1926-1995; Ferzetti, Gabriele, 1925-2015; Pavese, Cesare (Criterion collection, 2016)
A young woman returns to her home town of Turin to set up a new fashion salon and gets involved with a troubled woman and her three wealthy friends.